Kelimpahan Plankton di Perairan Pantai Kampung Enggros, Kota Jayapura - Albida Rante Tasak; Popi Ida Laila Ayer (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2019)
The aim of this research is to determine the abundance of plankton. This abundance has a tendency to explain the level of fertility in the sea waters of Enggros Village. The study was undertaken in April 2018.  The method of this study is using random sampling in four stations and these samples were analyzed in the Laboratory of Management of Coastal Resources, Ottow Geisler University, Jayapura.  The data from samples were analyzed by using excel software to describe the result from each station. The result showed that 7 genera of plankton consisting of 5 genera phytoplankton, namely Thalassionema, Pleurosigma, Skeletonema, Ceratium and 3 genera zooplankton they are Calanus sp, Clausocalanus sp, Acatia sp. The abundance of Thalassionema (177 sel/L) has significant at station I, while the abundance of Ceratium (22 sel/L) has lowest values at station III.  The total abundance of the plankton has fluctuated in each station. It was found that the total abundance of plankton was linear with the availability of nutrients and vice versa in the waters of Enggros villages.Keywords: Plankton abundance; Random sampling; Enggros Villages